2021
DOI: 10.1021/acs.jpcc.0c11380
|View full text |Cite
|
Sign up to set email alerts
|

Correct Structural Phase Stability of FeS2, TiO2, and MnO2 from a Semilocal Density Functional

Abstract: The structural phase stabilities of iron disulfide (FeS2), titanium dioxide (TiO2), and polymorphs of manganese oxides (MnO2) are known to be challenging problems for the semilocal exchange-correlation (xc) approximations of the Density Functional Theory. Popular and nonempirical semilocal xc functionals fail badly for at least one of these solids. For example, the strongly constrained and appropriately normed (SCAN) meta-GGA xc functional fails to predict the correct ground state for FeS2 (pyrite and marcasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Concerning MnO, it has been shown that the polymorphic structural energy difference computed using SCAN+rVV10+U , where U is determined from linear response theory, agrees very well with that obtained from DMC values 11 . Besides the SCAN-based methods, several other meta-GGA functionals are also proposed and tested for solid-state properties with consistently improved accuracy 45,[50][51][52][53][54][55][56][57][58][59][60][61] . Within those recent meta-GGAs, there are the functionals constructed from the cuspless hydrogen model [(r)MGGAC] 58,61 that show potential promising accuracy for different challenging problems in solid-state physics 50,60,61 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning MnO, it has been shown that the polymorphic structural energy difference computed using SCAN+rVV10+U , where U is determined from linear response theory, agrees very well with that obtained from DMC values 11 . Besides the SCAN-based methods, several other meta-GGA functionals are also proposed and tested for solid-state properties with consistently improved accuracy 45,[50][51][52][53][54][55][56][57][58][59][60][61] . Within those recent meta-GGAs, there are the functionals constructed from the cuspless hydrogen model [(r)MGGAC] 58,61 that show potential promising accuracy for different challenging problems in solid-state physics 50,60,61 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the SCAN-based methods, several other meta-GGA functionals are also proposed and tested for solid-state properties with consistently improved accuracy 45,[50][51][52][53][54][55][56][57][58][59][60][61] . Within those recent meta-GGAs, there are the functionals constructed from the cuspless hydrogen model [(r)MGGAC] 58,61 that show potential promising accuracy for different challenging problems in solid-state physics 50,60,61 . It is also quite an efficient semilocal functional that can predict band gaps of bulk and layered solids with reasonable accuracy 50,[61][62][63][64] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the SCAN, it was also recently proposed the MGGAC XC functional 80 , whose exchange part depends only on the α ingredient, being developed from a generalization of the Becke-Roussel approach 78,125 , and using the cuspless hydrogen model for the exchange hole density. The MGGAC functional showed its productive power over other meta-GGAs in terms of the band gap performance for bulk solids 126 , two dimensional (2D) van der Waals (vdW) materials 2,3,126 , and structural phase stability of solids 127 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, it is not one-electron self-interaction free, an important constraint that should be satisfied by every meta-GGA functional. Nevertheless, the MGGAC DFA has demonstrated several successes which include (i) improved thermochemical properties 80 , (ii) improved fundamental band gap for bulk and layer solids 126 , and (iii) correct energy ordering for challenging polymorphs of solids 127 . However, the functional has its own limitations such as moderate performance for lattice constants, bulk moduli, and cohesive energies for bulk solids 80 .…”
Section: Introductionmentioning
confidence: 99%
“…As of writing this thesis, a recent study reported that this well known dichotomy of the energy ordering of TiO 2 polymorphs is similar to the energy ordering of two other cases of compounds, namely for the polymorphs of MnO 2 and structural phase stabilities of iron disulfide, FeS 2 . In their study Patra et al [60] suggested this as a case where popular and nonempirical semilocal exchange correlation functionals fail to correctly describe their energetics. They found out that the recently proposed meta-GGA functional MGGAC can predict the correct ground state of these compounds along with a quantitative agreement of few of their other properties with experimental results.…”
Section: Discussionmentioning
confidence: 99%